THE EFFECT OF TRAINING OUTCOME PERCEPTION, PRODUCT KNOWLEDGE UNDERSTANDING AND WORK MOTIVATION ON SECURITY OFFICER EMPLOYEE PERFORMANCE AT PT MASS RAPID TRANSIT JAKARTA (PERSERODA) - Annisa, Suryani; Madiistriyatno, Harries; Taufiq, Kemal (Yayasan Pendidikan Cahaya Budaya Indonesia, 2025)
This research aims to examine the influence of perceptions of training outcomes, the level of product knowledge comprehension, and work motivation on the performance of security personnel at PT Mass Rapid Transit Jakarta (Perseroda). The study employed a quantitative approach. The sampling technique applied was non-probability sampling using an accidental sampling method. The sample size was determined using the Slovin formula, resulting in a total of 210 respondents. The research instrument used was a questionnaire, while the data analysis was conducted through multiple linear regression. The results of the analysis reveal that, partially, the perception of training outcomes has a positive and significant effect on the performance of security personnel. A similar finding was observed for product knowledge comprehension and work motivation, both of which demonstrated a positive and significant influence on employee performance. Simultaneously, these three variables—perceptions of training outcomes, product knowledge comprehension, and work motivation—also exert a significant effect on the performance of security personnel at PT Mass Rapid Transit Jakarta (Perseroda).